Comparing the effects of different amounts of fluid treatments in addition to analgesia in patients admitted to the emergency department with renal colic: A randomized study - ÖZPOLAT, ÇİĞDEM; SANRI, ERKMAN; AKOĞLU, HALDUN; DENİZBAŞI ALTINOK, ARZU (My University, 2022)
Objective: There are a limited number of studies examining the effect of fluid administration for acute pain relief in patients with renal colic. We aim to evaluate whether intravenous fluid of different amounts will make a difference regarding pain, in patients who presented to the emergency department (ED) with flank pain. Patients and Methods: This single-center, prospective, randomized clinical trial was performed at the ED of a university hospital. Subjects were randomly assigned to three groups. All received an intramuscular (IM) injection of 75 mg diclofenac sodium and 3 mg intravenous (IV) morphine. While group 1 did not receive extra treatment, group 2 received 100 cc /hr physiological serum (PS), and group 3 received 500 cc /hr PS. Pain was assessed by using the visual analogue scale (VAS) ruler for 6 hours. Results: A total of 201 patients were included. Mean age was 36.16 ± 9.85. At 60 min mean VAS scores were 3.55 ± 1.24 in the first group, 4.42 ± 1.87 in the second group and 5.02 ± 1.92 in the third group. In the group fluid not given, pain decrease was faster than others. At 240 min mean VAS scores were similar in all groups. Conclusion: This study indicates that IV fluids given to patients with renal colic pain was not effective in pain relief. Keywords: Renal colic, Analgesia, Intravenous fluid, Urolithiasis, VAS
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Renal colic; Analgesia; Intravenous fluid; Urolithiasis; VAS; PREVALENCE; GENDER; NEPHROLITHIASIS